Locale Detection, Identification And Significant Feature Extraction Of Brain Tumor By Manipulating Mr Images - D.AJU,; R.RAJKUMAR, (International Journal of Pharma and Bio Sciences, 2015)
Brain tumor is one of the most acute diseases that transpire the humans and a challenging field of medical sciences. Detection of the tumor is a challenging and demanding assignment due to its variations in type, size, location and shape. The main purpose of this scheme is to determine whether the MR image of a brain contains tumor and to locate it. A methodology to identify and determine the tumor in MR image is proposed and implemented in this paper. The method incorporates steps for enhancement, skull stripping, feature extraction and location of the tumor in the brain. The MR image is enhanced by removing its artifacts and the edges are preserved by applying filters on it. The unwarranted area such as the skull is removed by utilizing the skull stripping method. Various features are extracted for the identified tumor. And finally, the location of the tumor in the brain is located by equally dividing the brain image and is further named by its region.